The Use of Sodium Hypochlorite Solution for (n,γ)99Mo/99mTc Generator Based on Zirconium-Based Material (ZBM) - I. Saptiama; M Marlina; E. Sarmini; H Herlina; S Sriyono; A Abidin; H. Setiawan; K Kadarisman; H. Lubis; A. Mutalib (PPIKSN-BATAN, 2015)
The many problems in preparing fission product 99Mo led into this work to develop 99Mo/99mTc generator using neutron-irradiated natural MoO3 targets and, more specifically, to develop a zirconium-based material (ZBM) for chromatography columns that have an adsorption capacity of more than 100 mg Mo/g ZBM. This paper reports our recent experiments in the use of sodium hypochlorite solution of various concentrations to improve the yield of 99mTc in performance of (n,γ)99Mo/99mTc generators based on the ZBM. The synthesized ZBM was coated with tetraethyl orthosilicate for improving the hardness of the material. The adsorption of [99Mo]molybdate into ZBM was carried out by reacting ZBM into [99Mo]molybdate solution at 90°C to form ZBM-[99Mo] molybdate. ZBM-[99Mo]molybdate was then packed into generator column, then eluted with 10 × 1 mL of saline followed by 1 × 5 mL of NaOCl solution. The NaOCl solution concentrations used were 0.5%; 1%; 3%; and 5% for each column, respectively. This study resulted in a ZBM which has a 99Mo adsorption capacity of 167.5 ± 3.4 mgMo/g ZBM, as well as in a yield eluate of 99mTc of up to 70%, and the find that the optimum NaOCl concentration was 3%. The use of sodium hypochlorite solution affected 99Mo breakthrough. The higher sodium hypochlorite concentration used, the more 99Mo breaktrough exist on 99mTc eluate.Received: 22 October 2014; Revised: 21 April 2015; Accepted: 21 May 2015